Les bonobos se rappellent-ils la voix de leurs anciens partenaires ? - Florence Levréro; Sumir Keenan; Nicolas Mathevon; Jeroen MG Stevens; Jean Pascal Guéry; Klaus Zuberbühler (Revue de Primatologie)
In the present paper, we present our finding about the long-term vocal recognition of past social partners in bonobos Pan paniscus. These results have been published in 2016 in the journal Scientific Reports, 6:22046 | https://doi.org/10.1038/srep22046, and with the agreement of the co-authors, we propose here a French version on this study for the Revue de Primatologie. Long-term social recognition is vital for species with complex social networks, where familiar individuals can encounter one another after long periods of separation. For non-human primates who live in dense forest environments, visual access to one another is often limited, and recognition of social partners over distances largely depends on vocal communication. Vocal recognition after years of separation has never been reported in any great ape species, despite their complex societies and advanced social intelligence. Here we show that bonobos demonstrate reliable vocal recognition of social partners, even if they have been separated for five years. We experimentally tested bonobos’ responses to the calls of previous group members that had been transferred between captive groups. Despite long separations, subjects responded more intensely to familiar voices than to calls from unknown individuals—the first experimental evidence that bonobos can identify individuals utilizing vocalisations even years after their last encounter. Our study also suggests that bonobos may cease to discriminate between familiar and unfamiliar individuals after a period of eight years, indicating that voice representations or interest could be limited in time in this species.